Stock Returns, Expected Returns, and Real Activity. - Fama, Eugene F (Journal of Finance, 1990)
Measuring the total return variation explained by shocks to expected cash flows, time-varying expected returns, and shocks to expected returns is one way to judge the rationality of stock prices. Variables that proxy for expected returns and expected-return shocks capture 30 percent of the variance of annual NYSE value-weighted returns. Growth rates of production, used to proxy for shocks to expected cash flows, explain 43 percent of the return variance. Whether the combined explanatory power of the variables–about 58 percent of the variance of annual returns–is good or bad news about market efficiency is left for the reader to judge.